Farm-made feed for polyunsaturated fatty acids (pufas) rich carp production in India: a case study (SAARC Journal of Agriculture, 2018)
An 8 months feed demonstration program was conducted in the ponds of Ramakrishna Mission, Belur Math, West Bengal, India. The program aimed at providing hands-on training to trainees at Samaj Sevak Sikshan Mandir (SSSM) on farm-made feed formulation and use in aquaculture. Two ponds were selected, one at Shilpamandira of 0.1 h and fish were fed Feed-1, and another of 0.08 h at Samaj Sevak Sikshan Mandir (SSSM) and fed Feed-2. Indian major carps, Catla catla (catla) and Labeo rohita (rohu) were stocked at 4500 fish ha-1. The stocking size of rohu was 80-90g and of catla was 220-245g. Locally available low cost feed ingredients, rice bran, mustard oil cake, til oil cake and linseed oil sludge were used to formulate and prepare two farm-made mash feeds (Feed-1 and Feed-2). The fish were fed at 2% of total fish biomass in the ponds and were fed through bag feeding. At the end of the study rohu grew to 1.07 kg and catla to 1.6 kg in Shilpamandira pond (Feed-1), and rohu to1.5 kg and catla to 2.2 kg in Samaj Sevak Sikshan Mandir pond (Feed-2). The net production of fish was 4.9 and 6.8 t ha-1 for 8 months with Feed-1 and Feed-2, respectively. Dietary inclusion of linseed-oilsludge significantly increased the PUFA content in Indian major carps. The feed cost was substantially reduced by replacing mustard oil cake with til oil cake and incorporation of linseed oil sludge, a very low priced ingredient.SAARC J. Agri., 15(2): 45-55 (2017)